Validity and reliability of the Duruöz Hand Index in patients with psoriatic arthritis - DURUÖZ, MEHMET TUNCAY; ÖZ, NURAN; GEZER, HALİSE HANDE (My University, 2024)
Objective: The Duruöz Hand Index (DHI) is a valuable scale developed for evaluating hand functions of patients with rheumatoid arthritis and subsequently proven to be valid and reliable in various diseases. This study aims to investigate the validity and reliability of the DHI in patients with psoriatic arthritis (PsA). Methods: Patients diagnosed with PsA according to CASPAR criteria were enrolled. The demographic, clinical, and functional characteristics of patients were evaluated. Functional assessment was performed with DHI, Hand Functional Index, Health Assessment Questionnaire, and VAS-disability scale. C-reactive protein level, patients’ and physicians’ global VAS, swelling and tenderness of the hand joints, gross grip strength and thumb strength, and disease activity assessments were recorded as non-functional parameters related to active disease status. Reliability was assessed by internal consistency (with Cronbach’s-a) and test–retest intraclass correlation coefficient. Face, content, convergent, and divergent validities were applied. Results: One hundred and forty-four patients (74.3% female) were included in this study. The Cronbach’s alpha coefficient was 0.963, and for the test–retest reliability of the DHI, the intraclass correlation coefficient was 0.904 (p < 0.001). DHI showed good correlations with the functional disability scales (Hand Functional Index, Health Assessment Questionnaire, VAS-disability), indicating its convergent validity and moderate to non-significant correlations with the non-functional parameters supporting its divergent validity. Conclusions: Despite the occurrence of significant deformities and functional loss in PsA patients, there is a noticeable absence of specific tools tailored for PsA. Considering the intricacies associated with skin, nail, tendon, entheseal involvement, and arthritis, there is a need for straightforward tools in both clinical practice and studies involving patients with PsA. The DHI is a valid and reliable scale to evaluate the functional disability of hands in patients with PsA.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology; Duruöz Hand Index; Hand function; Outcome; Psoriatic arthritis